ASSESSMENT OF SOME HEAVY METALS IN POLICE TRAINING SCHOOL BARRACK STREAM, KADUNA STATE, NIGERIA - M.M. Babatunde; D. B.Samuel (Academy Journal of Science and Engineering)
This study was aimed at investigating the status of some heavy metal loads of barrack stream Kaduna, Nigeria. Monthly changes in heavy metals such as lead, chromium, nickel and cadmium were analyzed for a period of 3 months from November 2015 – January 2016. Concentration of Chromium (Cr), Cadmium (Cd), Lead (Pb) and Nickel (Ni) were determined by Standard Methods by APHA (1995) using Atomic Absorption Spectrophotometer. The results indicate lead (0.011±0.034),chromium (0.0001±0.63), cadmium (0.077±0.017) and nickel (0.002±0.056) were within the Federal Ministry of Environment (FMEnv) and Kaduna State Environmental Protection Authority, Nigeria. KEPA standards however, sample station A shows high concentrations of Cr while sample site C indicates concentrations above maximum permissible limits for Cd and Ni spatially. Therefore, this indicates that the water might not be good for drinking but may possibly be used for irrigation, fish farming and agricultural purposes after desisting from sewage and refuse disposal into the water bodies.